An important complication of a child with juvenile idiopathic arthritis: macrophage activation syndrome. (11th September 2013) - Reddy, Yuvaram N V; Bhatia, Navin; Scott, Julius Xavier; Nagarajan, Priyathersini
Abstract : A 4-year-old girl, a known case of juvenile idiopathic arthritis for 2 years presented to us with high-grade fever and abdominal distension for 2 months. On examination, her temperature was 104°F and she was found to be pale with bilateral cervical lymphadenopathy of up to 3×3 cm in size. Her liver was enlarged with a firm consistency and a span of 12 cm. Her spleen was enlarged up to 3 cm along its long axis. The rest of her systemic examination was normal. Laboratory investigations revealed leucocytosis, anaemia and thrombocytopenia with a mildly elevated erythrocyte sedimentation rate. Serum ferritin was 16 500 ng/dL and lactate dehydrogenase was 2311 U/L. A bone marrow aspirate showed macrophages showing ingested nuclei. She was diagnosed as having macrophage activation syndrome and was initiated on intravenous methylprednisolone 300 mg daily for 3 days and was switched over to oral prednisolone 2 mg/kg/day. She is currently doing well on follow-up.